Employing the Sunnah of the Prophet in treating behaviours and in thoughts Extremism and fanaticism - Abdulwahab, Prof.Dr. Rafida Sabah Abdulwahab; Abdullah, L. Shaimaa Mohammed Abdullah (Sulaimani Journal for Humanities, 2026)
The problem of extremism and fanaticism is considered one of the greatest and most dangerous problems facing Muslim society, as it leads to chaos, excommunication, and the killing of innocents. It is a disease and a plague that has afflicted the body of the Islamic nation, aiming to distort the image of true Islam. Therefore, we sought to find solutions and clarify the important role of educational institutions in confronting it.
Keywords: educational institutions; extremism; fanaticism; takfir